An Efficient Model for Low Voltage Distribution Smart Feeder Overcurrent Protection System Using Microcontroller. Issue 1 (May 2021) - Kumar, Akshay; Srivastava, Viranjay M.
Abstract: A Smart feeder is a growing energy distribution framework that is implanted with various types of energy distribution sources, as sustainable power sources, consolidated heat and power, and dispersed energy resources. The advantages of smart feeder arrangement are low transmission and dissemination cost, and, possibly, high dependability, high effectiveness, and low natural effect. Additionally, the administration of the electrical feeder system is getting increasingly problematic. The absence of data at the base feeder and the electricity administration network status have been distinguished as the significant obstruction to its successful monitoring and control of the electrical distribution system. This research work presents an advancement of the microcontroller-based smart feeder protection from overcurrent using fast using Solid State relay (SSR) to viable monitoring and control of the Feeder system. The simulation result of this work shows that the system is able to control and monitor the feeder protection system from overcurrent with the help of Microcontroller viable results that have been achieved with this system. In this research work, PhotoMOS relay cut-off time and overcurrent parameters have been calculated. The achieved results show significant results over the traditional EMR circuit protection. The PhotoMOS relay operating cut-off time 1.2, 1.3, and 1.4 ms with respect to the overcurrent values 0.8, 1.0, and 1.2 mA, which is significantly less than the EMR protection system. A 220 V electricity network was utilized to test the reliability and quality of the microcontroller-based PhotoMOS circuit. The proposed approach is demonstrated to be compelling in both grids associated and islanded modes.